The Characteristics and Influencing Factors of Rural Industrial Integration Land in China: A Case Study in Qingdao, Shandong Province - Bailin Zhang; Xueting Chen; Yan Zhou; Yining Zhang; Bingqian Zhai (Land)
Rural industrial integration land has emerged with the rise of new industries in rural China, exhibiting spatial distribution patterns distinct from traditional industrial land. However, research on this land use remains limited. This paper offers an exploratory definition of rural industrial integration land, takes three typical villages in Qingdao, Shandong Province as examples, establishes a model for measuring the diversity, complexity, and compatibility of land for industrial integration development based on the Hill numbers diversity measurement model, the information entropy index, and the mixedness index (WVMDIi) to explore the spatial layout characteristics of rural industrial integration land, and introduces the grey relational model to analyze its driving mechanism. The findings reveal that: (1) Rural industrial integration land is marked by structural diversity, multifunctionality, and compatibility in use. (2) From 2015 to 2023, the land’s diversity, complexity, and compatibility increased. The spatial layout characteristics of rural industrial integration land in the three villages, which integrates its diversity, complexity, and compatibility, increased from 1.3842, 1.5786, and 1.2127 to 1.8500, 1.9123, and 2.0224. (3) Between 2015 and 2019, key factors influencing spatial distribution included resource endowment, industrial foundation, and socioeconomic conditions. From 2019 to 2023, the most significant factors shifted to industrial foundation, farmers’ demand, and regional policies. Understanding the spatial distribution of rural industrial integration land is essential for guiding rural industrial spatial planning and promoting rural industrial revitalization.